Molecular epidemiology of porcine reproductive and respiratory syndrome virus in Central China since 2014: The prevalence of NADC30-like PRRSVs. (August 2017) - Wang, Lin-jian; Xie, Weitao; Chen, Xin-xin; Qiao, Songlin; Zhao, Mengmeng; Gu, Yu; Zhao, Bao-lei; Zhang, Gaiping
Abstract: Porcine reproductive and respiratory syndrome (PRRS), characterized by respiratory disorders in piglets and reproductive failure in sows, is still the great threat of swine industry. Recently, Emergence of the novel NADC30-like PRRS viruses (PRRSVs) has caused widespread outbreaks of PRRS. To investigate the epidemic characteristics of PRRSVs in Central China since 2014, 6372 clinical serum samples were tested by ELISA, 250 tissue samples were tested by RT-PCR, and among these, 30 ORF5 and 17 Nsp2 genes sequences were analyzed. Phylogenetic tree based on ORF5 revealed that, 17 isolates were clustered into subgroup 1, represented by the NADC30. And for the Nsp2, The strains which had a discontinuous 131-amino-acid deletion in Nsp2, called NADC30-like strains, were clustered into subgroup 2. Our data suggested that the NADC30-like PRRSV strains spread quickly and are now circulating and prevalent in Central China as well as the classical HP-PRRSV strains. In addition, amino acid variation analysis of GP5 revealed that the amino acid sequences of NADC30-like PRRSV strains underwent rapid evolution and contained extensive amino acid substitutions in important motifs, such as potential neutralization epitope and the N-glycosylation sites. In summary, our data would provide a large amount of detailed information on molecular variation and genetic diversity of PRRSV in central China. Highlights: The NADC30-like PRRSV strains have been circulating and prevalent in Central China. The classic HP-PRRSV strains are still circulating in pig farms of Central China and relatively conserved in recent years characterized by the highly similarity between each other. The NADC30-like PRRSV strains underwent rapid evolution and contained extensive amino acid substitutions in important motifs of GP5, such as major neutralizing epitope, potential N-glycosylation and signal peptides, which might be involved in viral virulence and immune escape. Our data would contribute to epidemiology investigation of PRRSV and have some implications for vaccine development.